An approach to compare performance of surgical masks for fighting against the COVID-19 pandemic. Issue 5 (4th May 2022) - Çelik, Ümit; Eren, Haluk
Abstract: Surgical masks are one of the most widely used personal protective equipment to keep pandemics under control. Medical face masks help slow the spread of the coronavirus (SARS-CoV-2) that causes COVID-19. Due to their lower cost and comfort, surgical masks are mostly preferred for the prevention of the epidemic. There are dozens of different face masks in the market. However, users do not have the opportunity to scientifically evaluate masks and analyze their performance against viruses. Surgical masks are classified according to EN 14683 standard but, the testing standards has been standardized considering bacterial permeability. In this study, a simple surgical mask testing approach has been demonstrated based on Quartz Crystal Microbalance (QCM) technique and variety of commonly available surgical masks' aerosol filtration performances were compared using the proposed approach. Then, SEM images of some masks were taken, and the results obtained from SEM analysis were compared with the results that was taken by proposed mask testing approach. In short, a simple direct mask test method taking into account the entire human aerosol distribution is proposed. Copyright © 2022 American Association for Aerosol Research Graphical Abstract: UF0001